Fungus Balls of the Bilateral Paranasal Sinuses - Lee, Dong Hoon (Springer India, 2012)
We describe the clinical and radiographic characteristics of fungus balls in the bilateral paranasal sinuses. The medical records of 8 of 245 patients with fungus balls of the bilateral paranasal sinuses between 2000 and 2010 were retrospectively reviewed. The incidence of bilateral paranasal sinus fungus balls was 3.3%. Fungus balls were located in the maxillary sinuses bilaterally in 4 cases (50%), followed by the maxillary sinus and contralateral sphenoid sinus in 3 cases (37.5%), and the sphenoid sinuses bilaterally in 1 case (12.5%). There were no predisposing anatomic variations for the occurrence of bilateral paranasal fungus balls. Although the presenting symptoms and signs were non-specific, CT findings were helpful in the diagnosis of bilateral fungus balls. Endonasal removal by an endoscopic approach was performed in all patients. No peri-operative complications or recurrences were noted. Fungus balls in the bilateral paranasal sinuses are most frequently found in the maxillary sinuses bilaterally. Because symptoms of bilateral paranasal fungus balls and findings on nasal endoscopic examination are frequently non-specific, a high index of suspicion is needed and imaging studies, such as CT, are essential to establish the correct pre-operative diagnosis.